2009
DOI: 10.1002/hbm.20810
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction and periventricular diffusion tensor changes in amnesic mild cognitive impairment and early Alzheimer's disease

Abstract: Our aim in this study was to explore the neural substrates of executive function in frontal and nonfrontal white matter using diffusion tensor imaging (DTI). We studied the relationship between executive dysfunction and DTI measurements on 13 subjects with amnesic mild cognitive impairment (aMCI), 11 subjects with early Alzheimer's disease (AD), and 16 control subjects. All participants underwent an examination of their intelligence, memory, and executive function and were subjected to DTI. Both aMCI and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 54 publications
5
60
2
1
Order By: Relevance
“…There is a growing body of evidence suggesting that active white matter degeneration underlies amnestic mild cognitive impairment (Rowley et al, 2013, Chen et al, 2009Gouw et al, 2008;Duan et al, 2006;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…There is a growing body of evidence suggesting that active white matter degeneration underlies amnestic mild cognitive impairment (Rowley et al, 2013, Chen et al, 2009Gouw et al, 2008;Duan et al, 2006;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…However, the analysis was not stratified by group. Chen, et al [43] examined the associations between FA and MD in the periventricular white matter (PVWM) and EF performance. They found that frontal PVWM was associated with performance on a verbal fluency test, the Wisconsin Card Sorting Test (WCST), and TMT B, while parietal PVWM was associated with perseverative errors on the WCST and TMT A.…”
Section: 4 Discussionmentioning
confidence: 99%
“…Within individual ROIs, the MCI group showed decreased FA in WM underlying the entorhinal, but not parahippocampal, cortex. Other studies have identified decreased WM integrity in parahippocampal WM in MCI (Liu et al, 2009; O'Dwyer et al, 2011; Rose et al, 2006; Zhang et al, 2007). One possible explanation for this discrepancy is that our sample may represent early MCI, as these are individuals who were neurologically normal per history, identified only by neuropsychological status.…”
Section: Discussionmentioning
confidence: 84%
“…WM integrity within posterior brain regions, most notably the posterior cingulate, is also related to memory (Delano-Wood et al, 2012; Fellgiebel et al, 2005; Rose et al, 2006; Walhovd et al, 2009). The importance of parietal WM to executive functioning in MCI has also been suggested (Chen et al, 2009; Jacobs et al, 2012; Kim et al, 2011). Because multiple studies show strong relationships between cortical thickness and cognition (Chang et al, 2010; Fjell et al, 2008; Walhovd et al, 2009), it is important to determine whether relationships between cognition and WM integrity are independent of cortical thinning.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation